2020
DOI: 10.3389/fgene.2020.598580
|View full text |Cite
|
Sign up to set email alerts
|

Improving Genomic Prediction of Crossbred and Purebred Dairy Cattle

Abstract: This study assessed the accuracy and bias of genomic prediction (GP) in purebred Holstein (H) and Jersey (J) as well as crossbred (H and J) validation cows using different reference sets and prediction strategies. The reference sets were made up of different combinations of 36,695 H and J purebreds and crossbreds. Additionally, the effect of using different sets of marker genotypes on GP was studied (conventional panel: 50k, custom panel enriched with, or close to, causal mutations: XT_50k, and conventional hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
4
17
0
1
Order By: Relevance
“…The study suggests that high accuracy for crossbreds would be achieved only with crossbred data in the reference population. Similar conclusions were reached by Khansefid et al (2020). In a study by Steyn et al (2021), the population included 90k Holsteins, 9k Jerseys, and <2k crosses.…”
Section: Symposium Review Geneticssupporting
confidence: 60%
See 1 more Smart Citation
“…The study suggests that high accuracy for crossbreds would be achieved only with crossbred data in the reference population. Similar conclusions were reached by Khansefid et al (2020). In a study by Steyn et al (2021), the population included 90k Holsteins, 9k Jerseys, and <2k crosses.…”
Section: Symposium Review Geneticssupporting
confidence: 60%
“…Reliabilities for an unrelated breed (Australian Red Cow) were low (0.23 for GBLUP and 0.27 for BayesR), indicating the small value of putative QTN on prediction across breeds. A study by Khansefid et al (2020) looked at the accuracy of genomic selection for various purebreds and crossbreds, with 3 types of SNP information and analyses either by GBLUP or by a Bayesian model. Predicted accuracies for crossbreds were the highest with the crossbred data.…”
Section: Symposium Review Geneticsmentioning
confidence: 99%
“…Adding informative variants for heat tolerance to the custom SNP panels as in [33] ensures that higher accuracies are achieved, which will help to drive genetic gain for this trait. Moreover, we expect that the genetic prediction of this trait would be sustained over generations when informative variants that are closer to the causal mutations are included in the custom SNP panels, as demonstrated by [35]. These authors found that using the custom XT_50k SNP panel, which contains prioritised sequence markers, gave a consistent and superior accuracy of predictions (compared to standard SNP panels) in crossbred cows (crossbreds represents "more distant relationships or many generations").…”
Section: Discussionmentioning
confidence: 96%
“…Adding informative variants for heat tolerance to the custom SNP panels as in [ 41 ] ensures that higher accuracies of prediction are achieved, which will help to drive genetic gain for this trait. Moreover, we expect that the genetic prediction of this trait would be sustained over generations when informative variants that are closer to the causal mutations are included in the custom SNP panels, as demonstrated by Khansefid et al [ 43 ]. These authors found that using the custom XT_50k SNP panel, which contains prioritised sequence markers, gave a consistent and superior accuracy of prediction (compared to standard SNP panels) in crossbred cows (crossbreds represents “more distant relationships or many generations”).…”
Section: Discussionmentioning
confidence: 99%